Which is the proper way of condensing this:
ln2-4ln3
Is it:
ln2+ln3^(-4)
or
ln2-ln3^4
Are either of these ways valid? And if so, which is the appropriate way? Or does that matter on the problem?
My other question.. Are these valid:
3^(x+1) = (3^x)*3
3^(x-1) = (3^x)/x or (3^x)(3^-1)
ln2+ ln 3^(-4)= ln[2(3^-4)]= ln(2/81)
ln2- ln 3^4= ln[2/3^4]= ln(2/81)
They are exactly the same.
Yes, 3^(x+1)= 3^x*3^1= (3^x)*3My other question.. Are these valid:
3^(x+1) = (3^x)*3
3^(x-1)= (3^x)(3^-1)= (3^x)/3. Is that what you meant instead of (3^x)/x?3^(x-1) = (3^x)/x or (3^x)(3^-1)